2023
DOI: 10.3390/ijms241210210
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Does Not Affect the miRNA Cargo of Bovine Raw Milk Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) and their microRNA (miRNA) cargo have been proposed as possible mammary gland health biomarkers in cattle. However, throughout the day, the biologically active milk components, such as miRNAs, may change due to the dynamic nature of milk. The current study aimed to evaluate the circadian fluctuation of milk EVs miRNA cargo to assess the feasibility of milk EVs as future biomarkers for mammary gland health management. Milk from four healthy dairy cows was collected for four consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This finding is consistent with emerging evidence that there is diurnal variation in both EVP release and EVP cargo and highlights the importance of accounting for the time of day of blood collection in studies of circulating EVP miRNAs during pregnancy [23,24,38]. In contrast with plasma, we did not observe an association between the time of day of milk collection and EVP miRNA composition, consistent with a prior study of bovine milk [39]. Although a previous study of predominantly Hispanic participants in Los Angeles also reported that the levels of many miRNAs change in maternal circulation across gestation [7], we did not observe an association between gestational age at plasma collection and EVP miRNA composition in this pilot study.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with emerging evidence that there is diurnal variation in both EVP release and EVP cargo and highlights the importance of accounting for the time of day of blood collection in studies of circulating EVP miRNAs during pregnancy [23,24,38]. In contrast with plasma, we did not observe an association between the time of day of milk collection and EVP miRNA composition, consistent with a prior study of bovine milk [39]. Although a previous study of predominantly Hispanic participants in Los Angeles also reported that the levels of many miRNAs change in maternal circulation across gestation [7], we did not observe an association between gestational age at plasma collection and EVP miRNA composition in this pilot study.…”
Section: Discussionsupporting
confidence: 92%
“…Murine lung-derived EVs were shown to have circadian rhythm related differences in uptake and functionality in an in vitro model using mouse-derived primary whole bone marrow cells 104 . In contrast, milk-derived EVs from cows showed no difference in EVs or miRNA cargoes over the course of the day 105 . This discrepancy may be due to the difference between milk and blood, where milk is stored in alveoli before being released to the cistern, allowing for EVs to be stored.…”
Section: Mrna Cargoes As Biomarkers Of Diseasementioning
confidence: 79%
“…21 Furthermore, it has been recently indicated that the miRNA content in miEVs is consistent throughout the day, suggesting their potential role as diagnostic tools for assessing the health of the mammary glands. 146 diagnostic biomarkers for the early detection of mammary gland infection. In another study, Ma et al evaluated the miEVs from three healthy and six S. aureus-infected bovines and identified 37 differentially expressed miRNAs, among which bta-miR-378 and bta-miR-185 had a significantly higher level in miEVs from S. aureus infected bovines.…”
Section: Intestinal Healthmentioning
confidence: 99%
“…Because miEVs content is protected from degradation by the bilayer membrane and reflects the health status, use of them as diagnostic, prognostic, and predictive biomarkers is currently very popular . Furthermore, it has been recently indicated that the miRNA content in miEVs is consistent throughout the day, suggesting their potential role as diagnostic tools for assessing the health of the mammary glands . Sun et al analyzed the expression profile of miEVs miRNAs in noninfected and Staphylococcus aureus ( S. aureus ) infected cattle .…”
Section: Biomedical Applications Of Mievsmentioning
confidence: 99%